Supplementation of L-Ornithine Could Increase Sleep-like Behavior in the Mouse Pups - Mayumi Takakura; Satsuki Nagamachi; Takuma Nishigawa; Yoshihiro Takahashi; Mitsuhiro Furuse (Metabolites, 2022)
Along the maternal–fetal–neonatal axis, one of the problems relating to the maternal–neonatal axis is infant sleep problems including nighttime crying. One possible solution could be to provide the newborn with sleep-promoting ingredients through breast milk or formula. So far, it has been reported that L-ornithine has a sleep-related effect. Therefore, we investigated the effect of dietary L-ornithine on maternal mouse plasma and milk L-ornithine levels in Experiment 1. In Experiment 2, a single dose of L-ornithine was applied to know the time-course changes in plasma, mammary gland and milk L-ornithine levels. Experiment 3 was conducted to confirm sleep behavior as well as changes in polyamine levels in milk. L-Ornithine levels in maternal plasma significantly increased by both dietary regimen and single oral administration in Experiments 1 and 2. Both L-ornithine treatments also increased its levels in milk, although not to a concentration as high as in plasma. In Experiment 3, the level of polyamines, which are metabolized from L-ornithine, did not significantly differ after L-ornithine administration. In sleep-like behavior observations, the average concentration of L-ornithine in milk did not increase the sleep-like behavior of mouse pups. However, more concentrated L-ornithine solutions can significantly increase sleep-like behavior. These results revealed that even if mothers ingested L-ornithine to increase L-ornithine levels in breast milk, it is difficult to promote sleep in newborns. Because it is difficult to raise L-ornithine in breast milk to sleep-inducing levels, L-ornithine added formula may partially improve infant sleep and has the potential for preventing infant sleep problems such as nighttime crying.